2016
DOI: 10.1155/2016/8648190
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatitis and Pancytopenia in Healthy Infant with Adenovirus

Abstract: Adenoviruses are a common cause of respiratory infection, pharyngitis, and conjunctivitis in infants and young children. They are known to cause hepatitis and liver failure in immunocompromised patients; they are a rare cause of hepatitis in immunocompetent patients and have been known to cause fulminant hepatic failure. We present a 23-month-old immunocompetent infant who presented with acute noncholestatic hepatitis, hypoalbuminemia, generalized anasarca, and pancytopenia secondary to adenovirus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“… 2 4 Some case reports also show that these respiratory viruses can cause liver injury during systemic infection. 9 10 11 12 13 14 In addition to viruses, bacterial pneumonia (e.g., Streptococcus pneumonia , Haemophilus influenza , Staphylococcus aureus , or Pseudomonas aeruginosa ) and mycoplasma pneumonia can cause hepatocellular damage and cause laboratory abnormalities, including hyperbilirubinemia. 1 …”
Section: Discussionmentioning
confidence: 99%
“… 2 4 Some case reports also show that these respiratory viruses can cause liver injury during systemic infection. 9 10 11 12 13 14 In addition to viruses, bacterial pneumonia (e.g., Streptococcus pneumonia , Haemophilus influenza , Staphylococcus aureus , or Pseudomonas aeruginosa ) and mycoplasma pneumonia can cause hepatocellular damage and cause laboratory abnormalities, including hyperbilirubinemia. 1 …”
Section: Discussionmentioning
confidence: 99%
“…Previous Korean studies also reported that respiratory infection was the most common infection focus in NRH; however, adenovirus and respiratory syncytial virus were more common than rhinovirus (2,4). Some case reports also show that these respiratory viruses can cause liver injury during systemic infection (5)(6)(7)(8)(9)(10). In addition to viruses, bacterial pneumonia (e.g., Streptococcus pneumonia, Haemophilus in uenza, Staphylococcus aureus, or Pseudomonas aeruginosa) and mycoplasma pneumonia can cause hepatocellular damage and cause laboratory abnormalities, including hyperbilirubinemia (1).…”
Section: Discussionmentioning
confidence: 97%
“…We found that the older age of patients was related to a shorter duration of hepatic enzyme elevation; the mean age of our study patients was 3.5 years, and 311 (50.7%) were younger than 12 months. Other studies have also shown that children younger than 5 years commonly experience increased liver enzyme levels during systemic infections (4,5,8,11,12). As the exact mechanism of NRH remains unknown, the explanation of the poorer prognosis in younger infants is even more di cult.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that these abnormal laboratory test results were partly related to adenovirus infection and partly related to their underlying diseases. For example, adenovirus infection could result in hepatitis and pancytopenia [11].…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that these abnormal laboratory test results were partly related to adenovirus infection and partly related to their underlying diseases. For example, an adenovirus infection could result in hepatitis and pancytopenia [ 11 ]. Therefore, it is reasonable that hypoalbuminaemia, anaemia and thrombocytopaenia could present in RAI patients.…”
Section: Discussionmentioning
confidence: 99%